Ion exchange derived CsPbBr3:Mn nanocrystals with stable and bright luminescence towards white light-emitting diodes. (September 2022) - Liu, Yanping; Zhao, Yubin; Zhu, Yuanna; Zhan, Yan; Matras-Postolek, Katarzyna; Yang, Ping
Highlights: Mn:CsPbBr3 perovskite nanocrystals (NCs) revealed high green-emission at 520 nm under 365 nm excitation. The photoluminescence quantum yields increased from 62.4 to 82.9% after Mn doping. The luminescence of Mn 2+ ions was observed by benzoyl chloride reprocessing adjusting band gap. Abstract: CsPbBr3 :Mn NCs were synthesized via a hot injection method to test the anion exchange reaction using ZnCl2 and benzoyl chloride. In the case of no ion exchange reaction, Mn-doping resulted in the photoluminescence (PL) efficiency of the NCs increased from 62.4 to 82.9% and the stability greatly improved even though no Mn emission was observed. The NCs maintained the initial cubic phase structure. Interestingly, the ion exchange reaction using benzoyl chloride resulted in the host excitation to Mn 2+ d-d transition. Bright Mn ion orange-emission was observed. The mild ion exchange reaction of benzoyl chloride greatly improved the stability of the NCs compared with ZnCl2 . To use the bright Mn ion emission, a white light-emitting diodes (LED) with a color coordinates of (0.320, 0.319) and color temperature of 5706 K was created using CsPbBr3 :Mn NCs. The result provides an effective route to obtain high-performance white LED materials. Graphical abstract: Image, graphical abstract